Chromosomal jumping from the DXS165 locus allows molecular characterization of four microdeletions and a de novo chromosome X/13 translocation associated with choroideremia. - Cremers, F P (1989)
Choroideremia (tapeto-choroidal dystrophy, TCD), an X chromosome-linked disorder of retina and choroid, causes progressive nightblindness and central blindness in affected males by the third to fourth decade of life. Recently, we have been able to map the TCD gene to a small region of overlap between five different, male-viable Xq21 deletions that were found in patients with TCD and other clinical features. Two families were identified in which classical, nonsyndromic TCD is associated with small interstitial deletions that are only detectable with probe p1bD5 (DXS165). To characterize these and two other deletions that were identified more recently, we have used the chromosome walking and jumping techniques to generate a set of five chromosomal-jumping clones flanking the DXS165 locus at various distances. With these clones, we could localize four of the eight deletion endpoints and the breakpoint on the X chromosome of a female with a de novo X/13 translocation and choroideremia. These studies assign the TCD gene, or part of it, to a DNA segment of only 15-20 kilobases.